Comparison of Efficacy And Safety of Isotretinoin Versus Lymecycline Capsule For The Treatment of Acne Vulgaris - Aslam, Azmiree Binte; Haque, Mohammad Anwarul; Abdullah, Mohammad Shayekh (Journal of Dhaka Medical College, 2024)
Background: Acne vulgaris is a very common condition which can cause significant physical and psychological morbidity. Oral retinoids and tetracyclines have a major role in acne treatment. Isotretinoin (13-cis-retinoic acid) is the only therapy that impacts on all of the major aetiological factors implicated in acne. Another agent is lymecycline, a tetracycline antibiotic have an antibacterial action against P. acnes and also an anti-inflammatory action and used for treatment of acne. Objectives: To determine the efficacy and safety of Isotretinoin capsules versus Lymecycline capsule in treatment of mild to moderate facial acne vulgaris. Materials & method: This open labelled, randomized study was conducted in Department of Dermatology and Venereology, Dr. Sirajul Islam Medical College & Hospital Ltd., Dhaka, from December 2021 to May 2022. Patients of mild to moderate facial acne vulgaris were enrolled for study. Clinical examination and relevant investigation were done meticulously. A total number of 50 patients was selected and randomization was done 1:1 parallel design into two groups (group-A and group-B), each of which included 25 patients. Group A patients received Isotretinoin and group B patients were given Lymecycline. Patients were followed up on 2nd, 4th, 8th and finally on 12th week to see clinical improvement and adverse effects. All information was recorded in data collection sheet. Result: The mean age was found 20.4±5.7 years in group A and 19.9±6.9 years in group B. The mean age difference was not statistically significant (p>0.05) between two groups. Male to female ratio was almost 1:3 in the whole study patients. Mean score for open comedone (0.28±0.22 vs. 2.2±1.13), closed comedone (1.92±0.19 vs. 2.08±0.25), papule (0.82±0.29 vs. 1.27±1.04) and pustule (0.85±0.33 vs. 1.19±0.39) was identical in group-A and B respectively and significantly better reduction of acne score (p=0.001) in the group A than the group B. It was evident that abdominal discomfort (4.0% vs. 32.0% in group A & B), diarrhea (0% vs. 16.0% in group A & B) and photosensitivity (4.0% vs. 16.0% in group A & B) was predominant in group B. The difference was statistically significant (p=0.029). Whereas, erythema and burning was predominant in group A. Mean burning was found 0.15±0.08 in group A and 0.11±0.05 in group B and mean scaling was found 1.27±0.98 in group A and 1.45±0.98 in group B which were statistically non significant (p>0.05) between two groups. At 4th follow up mean total safety score was found 3.05±0.92 in group A and 4.65±1.25 in group B. Conclusion: Isotretinoin was as effective as lymecycline for the treatment of moderately severe acne vulgaris. Both treatments were well tolerated & effective. J Dhaka Med Coll. 2023; 32(1) : 63-70